Territorial Analysis of Urban Environmental Problems: The Case of Facatativa Municipality, Cundinamarca, Colombia (1980-2010) (2019)
The current environmental situation of Facatativa municipality’s urban area, is the response to historical events that have been presented in the face of processes of territorialization, expressed in the phenomena of urbanization and industrialization. In order to understand the environmental problems in the Facatativa municipality’s urban area based on its territorial analysis, the territorial configuration in the municipality’s urban space between 1980 and 2010 has been analyzed from a geohistorical, geopolitical and environmental approach. It was observed that the municipality has been presenting complex environmental problems that have repercussions in the recognition of the value of the environment and natural resources, in the quality of life and in the environmental sustainability. In this sense, territorial environmental management becomes the strategy to provide the guidelines for planning the territory, promoting equality, equity and sustainable development.